The effect of an out-of-school mindfulness program on adolescents’ stress reduction and emotional wellbeing - Carreres Ponsoda, Federico (Cuadernos de Psicología del Deporte, 2017)
In recent years schools and youth-serving organizations have progressively adopted programs to reduce adolescents’ stress levels and improve optimism trough mindfulness interventions. The aim of this study was to examine the effects of a mindfulness out-of-school program for adolescents, on perceived levels of stress, optimism and mindfulness skills. Thirty adolescents (15 girls and 15 boys), aging from 16 to 18 years old (M = 16.8) were randomly allocated to either 8-week mindfulness extracurricular program (n = 15; 8 girls and 7 boys) or a control group (n = 15; 7 girls and 8 boys). The results demonstrate that participants in the intervention group reported reductions in perceived stress and increases in levels of optimism and in five specific mindfulness skills. These findings suggest that using an out-of-school mindfulness program may be an effective setting to teach adolescents to use mindfulness to manage stress and to cultivate more positive emotional and social skills. This study is therefore significant for encourage the implementation of out-of-school mindfulness program that contribute to positive youth development and for an improvement of their health and more holistic health and well-being.